IV International Congress of Innovation and Sustainable ICONIS (4th : 2020 Octubre 22-23 : León (Guanajuato, Mexico)) - International Congress of Innovation and Sustainable ICONIS (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Spa: The fourth international congress of Innovation and Sustainability is coorganized by the Red Iberoamericana para la Competitividad, Innovacion y Desarrollo (REDCID), Universidad de la Salle Bajio (Mexico), Universidad Michoacana de San Nicolas de Hidalgo (Mexico), Universidad Pedagógica y Tecnológica de Colombia (Colombia). The congress will provide a forum for researchers, academics and students to discuss research ideas and present recent advances in different topics.